Predicting EFL Teachers’ Pedagogical Digital Competence Through Growth Mindset and Peer-Coaching Experience - Rezazadeh Jabalbarezi, Amir Hossein (Assessment and Practice in Educational Sciences, 2025)
The increasing integration of digital technologies into educational settings has intensified the need for teachers to develop pedagogical digital competence. In EFL contexts, teachers are expected not only to possess linguistic and pedagogical knowledge but also to integrate digital technologies into instruction in pedagogically meaningful ways. Despite growing research on digital competence, limited attention has been paid to the psychological and collaborative factors that may contribute to its development, particularly in the Iranian EFL context. Therefore, the present study investigated whether growth mindset and peer-coaching experience significantly predict Iranian EFL teachers’ pedagogical digital competence. Employing a quantitative descriptive–correlational design, the study was conducted with 150 EFL teachers selected through convenience sampling. Data were collected using questionnaires measuring pedagogical digital competence, growth mindset, and peer-coaching experience. The instruments were validated through expert review, and their reliability was confirmed using Cronbach’s alpha coefficients. The data were analyzed through descriptive statistics, Pearson correlation, and multiple regression analysis. The findings revealed significant positive relationships among growth mindset, peer-coaching experience, and pedagogical digital competence. Moreover, both growth mindset and peer-coaching experience significantly predicted pedagogical digital competence, with growth mindset demonstrating the stronger predictive role. The findings suggest that teachers’ digital pedagogical development may be influenced not only by technical knowledge and access to technology but also by adaptive professional beliefs and collaborative learning experiences. The study offers implications for teacher education programs, professional development initiatives, and future research on digital competence in EFL settings.